2011
DOI: 10.1517/14712598.2011.616889
|View full text |Cite
|
Sign up to set email alerts
|

AE37: a novel T-cell-eliciting vaccine for breast cancer

Abstract: Clinical trials have shown the AE37 vaccine to be safe and capable of generating peptide-specific, durable immune responses. This has been shown in patients with any level of HER-2/neu expression. Early clinical findings suggest there may be benefit to AE37 vaccination in preventing breast cancer recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…The vaccine was found to be safe and well tolerated, and demonstrated benefits in patients with HER2 non-over expressing tumours, especially those with triple negative disease, where the 5-year relative risk reduction for recurrence reached 35%. In a separate sub study conducted in our laboratory, we found that pre-existing immunity either as in vitro (levels of IFNγ) or in vivo (dermal reaction) parameter, might serve as a predictive biomarker for clinical response in patients vaccinated with AE37 [74][75][76]. …”
Section: The Ae37 Therapeutic Cancer Vaccine Paradigmmentioning
confidence: 92%
“…The vaccine was found to be safe and well tolerated, and demonstrated benefits in patients with HER2 non-over expressing tumours, especially those with triple negative disease, where the 5-year relative risk reduction for recurrence reached 35%. In a separate sub study conducted in our laboratory, we found that pre-existing immunity either as in vitro (levels of IFNγ) or in vivo (dermal reaction) parameter, might serve as a predictive biomarker for clinical response in patients vaccinated with AE37 [74][75][76]. …”
Section: The Ae37 Therapeutic Cancer Vaccine Paradigmmentioning
confidence: 92%
“…This may be due to the heavy tumor burden which generates a hostile tumor microenvironment with a plethora of suppressor elements dampening antitumor responses. To circumvent this issue, recent clinical trials were performed with patients at the adjuvant setting with minimal residual disease and a high risk of relapse [14]. The rationale behind vaccination in this clinical setting is that patients with minimal tumor burden still have a fully competent immune system capable of developing robust antitumor responses.…”
Section: Cancer Vaccines: Limited Success But the Research Should Remmentioning
confidence: 99%
“…These moved into early-phase clinical studies in the first decade of the 2000s including: several early-phase clinical studies of the immunodominant E75 peptide with granulocyte macrophage colony-stimulating factor as a biological adjuvant (now referred to as NeuVax™) [221][222][223]; of an improved E75 vaccine, AE37 (NCT00524277) [224][225][226][227]; and of the subdominant G2 peptide (NCT00524277) [228][229][230]. Other groups have ongoing Phase I and II clinical studies examining other peptides, other adjuvants and/or combinations of immunomodulatory agents (NCT00058526, NCT00194714, NCT00791037, NCT00952692, NCT01355393, NCT01376505 and NCT01632332).…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%